The Paradox of Halal Branding: Navigating Religious Sincerity and Market Commodification in Indonesia's Middle-Class Economy - Aziz, Muhammad; Sholikah, Sholikah; Mujrimin, Bayu; Ghazali, Mohd Fahmi (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2026)
Abstract: Prologue: Halal branding in Indonesia has evolved beyond a religious requirement into a complex arena where spiritual authenticity intersects with market commodification. While intended to embody ethical compliance, the proliferation of halal labels among the expanding Muslim middle class has transformed